2010
DOI: 10.1093/ndt/gfq603
|View full text |Cite
|
Sign up to set email alerts
|

Fresh and cryopreserved, uncultured adipose tissue-derived stem and regenerative cells ameliorate ischemia–reperfusion-induced acute kidney injury

Abstract: Background. Acute kidney injury (AKI) represents a major clinical problem with high mortality and limited causal treatments. The use of cell therapy has been suggested as a potential modality to improve the course and outcome of AKI.Methods. We investigated the possible renoprotection of freshly isolated, uncultured adipose tissue-derived stem and regenerative cells (ADRCs) before and after cryopreservation in a rat ischemia–reperfusion (I–R) model of AKI.Results. We demonstrated that ADRC therapy drastically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 48 publications
4
74
1
Order By: Relevance
“…Wnt agonist treatment, however, resulted in renal Ki67 staining patterns that closely resembled sham animals. Our observation echoes a recent demonstration that Ki67 staining in kidney tubular cells is indicative of renal regeneration and proliferation following IR in rats (26). This suggests that treatment with Wnt agonist may represent a successful means of upregulating regenerative pathways that are crucial to recovery following severe renal insult.…”
Section: Discussionsupporting
confidence: 88%
“…Wnt agonist treatment, however, resulted in renal Ki67 staining patterns that closely resembled sham animals. Our observation echoes a recent demonstration that Ki67 staining in kidney tubular cells is indicative of renal regeneration and proliferation following IR in rats (26). This suggests that treatment with Wnt agonist may represent a successful means of upregulating regenerative pathways that are crucial to recovery following severe renal insult.…”
Section: Discussionsupporting
confidence: 88%
“…But other studies have demonstrated that stem cells contribute to the regenerative process by producing protective and regenerative factors rather than directly using their differentiated progeny to replace damaged cells. [44][45][46][47] Our data indicate that cytokine-induced mobilization is effective in gentamicin-induced ATN, but our current study could not tell that the partial morphologic and functional improvements were due to multiple differentiation of bone marrow-derived cells or secretion of stimulatory or regenerative factors. Meanwhile, bone marrow contains various types of stem cells.…”
Section: Discussioncontrasting
confidence: 63%
“…These data are consistent with other studies that suggest a role for ADRCs in reducing local inflammation. 12,13 Blood vessel formation (angiogenesis) plays an important role during the wound healing process. In this study, both local injection and spray delivery of ADRCs equally increased microvessel density within the wound tissue after burn injury.…”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, our group has previously shown that ADRC treatment downregulates inflammatory-related gene expression (interleukin 6 and CXC chemokine ligand 12 ) in a rat model of acute kidney injury. 13 We have also reported that seeding ADRCs onto a widely used collagen dermal substitute increases wound angiogenesis, blood vessel maturation, and matrix remodeling. 11 On the basis of studies such as these, the use of ADRCs as an adjunct to healing has advanced worldwide into multiple clinical trials (e.g., NCT0232696, 14,15 NCT01813279, 16 and NCT02052427 17 ).…”
Section: Introductionmentioning
confidence: 90%